2019 International Joint Conference on Neural Networks (IJCNN) 2019
DOI: 10.1109/ijcnn.2019.8852059
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle Re-identification: an Efficient Baseline Using Triplet Embedding

Abstract: 1 In this paper we tackle the problem of vehicle reidentification in a camera network utilizing triplet embeddings. Re-identification is the problem of matching appearances of objects across different cameras. With the proliferation of surveillance cameras enabling smart and safer cities, there is an ever-increasing need to re-identify vehicles across cameras. Typical challenges arising in smart city scenarios include variations of viewpoints, illumination and self occlusions. Most successful approaches for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 43 publications
0
61
0
Order By: Relevance
“…For the vehicle ReID problem, the recent work [18] explores the advances in batch-based sampling for triplet embedding that are used for state-of-the-art in person ReID solutions. They compared different sampling variants and demonstrated state-of-the-art results on all vehicle ReID benchmarks [28,26,52], outperforming multi-view-based embedding and most spatio-temporal regularizations (see Tab.…”
Section: Image-based Reidmentioning
confidence: 99%
“…For the vehicle ReID problem, the recent work [18] explores the advances in batch-based sampling for triplet embedding that are used for state-of-the-art in person ReID solutions. They compared different sampling variants and demonstrated state-of-the-art results on all vehicle ReID benchmarks [28,26,52], outperforming multi-view-based embedding and most spatio-temporal regularizations (see Tab.…”
Section: Image-based Reidmentioning
confidence: 99%
“…The key practices include hard triplet mining, pretraining for identity classification, dataset augmentation with difficult examples, sufficiently large image resolution, and state-of-theart base architecture. Triplet mining and ID classification have been already adopted in vehicle Re-ID [13], [14]. Kumar et al [14] demonstrated an extensive evaluation of contrastive and triplet losses during vehicle Re-ID.…”
Section: A Re-identification (Re-id)mentioning
confidence: 99%
“…Triplet mining and ID classification have been already adopted in vehicle Re-ID [13], [14]. Kumar et al [14] demonstrated an extensive evaluation of contrastive and triplet losses during vehicle Re-ID.…”
Section: A Re-identification (Re-id)mentioning
confidence: 99%
“…Some recent works [17,19,22] combined the classification loss through metric learning. Kumar et al [9] conducted an indepth analysis of the vehicle triplet embeddings, extensively evaluated the loss function, and proved that the use of triplet embeddings is effective.…”
Section: Loss Functions For Embeddingmentioning
confidence: 99%